Miracle Cure - Coben, Harlan (UK Orion, 1991)
They were looking for a miracle cure... Sara Lowell and Michael Silverman are the ideal celebrity couple, darlings of the media. She's TV's most popular journalist. He's New York's hottest basketball star. Their lives would soon be shattered by the most deadly illness of modern times. Dr. Harvey Riker's clinic has found the miracle cure that millions seek. One-by-one his patients are getting well. One-by-one they are targeted by a serial killer more fatal than their disease. Rev. Earnest Sanders' ultra-conservative Holy Crusade Church saw the disease as God's vengeance on a lustful, sin-ridden generation of the damned. And God's will could not be denied. Lieutenant Bernstein's true desires make him a perfect choice to track the killer...or a perfect victim.
Keywords: Fiction / Crime, Fiction / Mystery & Detective / General, AIDS (Disease) -- -- Fiction, AIDS (Disease) -- Fiction -- Patients, Detective and mystery stories